Prevalence and associated factors of probable depression amongst pregnant and parenting young females: a comparison of adolescents and young adults in rural South Africa - Seakamela, K. P.; Mashaba, R. G.; Ntimana, C. B.; Mbombi, M. O.; Tlouyamma, J.; Mphekgwana, P.; Nemuramba, R.; Mothapo, K.; Muthelo, L.; Mabila, L. N.; Dhau, I.; Maimela, E. (Frontiers in Child and Adolescent Psychiatry, 2023)
Background Pregnant teenagers have been reported to have an increased likelihood of experiencing depression than their non-pregnant peers. There is little research on the risk factors for depression in rural Black adolescents and young adults, especially after the Covid-19 pandemic. Therefore, the current study aimed to identify the prevalence of probable depression and associated factors amongst pregnant and parenting young females. Method The study was a cross-sectional design, consisting of 362 pregnant and parenting adolescents and young adults aged 14–22. The study used the Edinburgh Postnatal Depression Scale (EPDS) to measure probable depression. Data were analyzed using Statistical Package for Social Sciences SPSS, version 27.0. Results The study found that the overall prevalence of probable depression was 42.8%. The study also found a relationship between alcohol consumption, lack of financial support, unplanned pregnancy, and probable depression in pregnant and parenting adolescents. The prevalence of unplanned pregnancy in the present study was 81.8%. Conclusion Furthermore, the present study indicated that participants from low socio-economic status families and those who were HIV positive were at a greater risk of depression in both groups. Therefore, we recommend that measures be put in place for early detection and treatment of depression and that social support be given to adolescent mothers.